73.5k views
4 votes
Find the inverse of the given function

Find the inverse of the given function-example-1

1 Answer

1 vote

For this case, we must find the inverse of the following function:


f (x) = \frac {5x + 1} {- x + 7}\\x\\eq 7

To find the inverse we follow the steps below:


y = \frac {5x + 1} {- x + 7}

We rewrite the denominator:


y = \frac {5x + 1} {- (x-7)}\\y = - \frac {5x + 1} {(x-7)}

We exchange variables:


x = - \frac{5y + 1} {(y-7)}

We solve for y:

We multiply on both sides of the equation by (y-7)


x (y-7) = - 5y-1\\xy-7x = -5y-1

We subtract xy on both sides of the equation:


-7x = -5y-1-xy

We add 1 to both sides:


-7x + 1 = -5y-xy

We factor for y:


-7x + 1 = y (-5-x)

We divide both sides by (-5-x):


y = \frac {-7x + 1} {- 5-x}

So, we have:


f ^ {- 1} (x) = \frac {-7x + 1} {- 5-x}

Answer:


f ^ {- 1} (x) = \frac {-7x + 1} {- 5-x}


x\\eq -5

User Nassima
by
5.3k points